Synergism of cellulosic nanowhiskers and graft structure in stereocomplex-based materials: formation in solution and a stereocomplex memory study - Purnama, Purba; Kim, Soo Hyun (SPRINGER, 2014)
Stereocomplexation is one of the approaches to improve polylactide's properties. Along with improving its properties, it also limits stereocomplex formation through solution and stereocomplex memory. The graft structure and presence of nanoparticles have a synergetic effect, improving the stereocomplex formation and its memory. The bio-stereocomplex-nanocomposite materials are generated by stereocomplexation of polylactide-graft-acetylated cellulosic nanowhiskers in thes solution. The graft structure containing well-distributed acetylated cellulose nanowhiskers results in unusual stereocomplexation in the solution and influences the stereocomplex memory of the bio-stereocomplex-nanocomposite materials. Perfect stereocomplexes are easily obtained in a relatively short mixing time (5 min) from various solution concentrations up to 20 % (w/v). The bio-stereocomplex-nanocomposites have excellent stereocomplex memory to re-form the stereocomplex after melting, which is the main limitation of stereocomplex materials in industrial processes. This fully bio-based material is a potential ecofriendly candidate for the future.
Keywords: ENANTIOMERIC POLY(LACTIC ACID)S; MECHANICAL-PROPERTIES; POLYLACTIDE; CRYSTALLIZATION